Pengaruh Inflasi, Suku Bunga BI 7-Day (Reverse) Repo Rate Dan Nilai Tukar Rupiah Terhadap Indeks Harga Saham Gabungan - Lidya Martha; Bambang Simbara (JURNAL PUNDI, 2021)
Fast traslate Icon translate The purpose of this study is to examine the effect of inflation, 7-Day (reverse) Repo Rate and Rupiah Exchange Rate on the Composite Stock Price Index listed on the IDX. The study population is the entire Stock Price Index in the IDX period August 2016 - December 2019. The sample was selected using the purposive sampling method with sample criteria is all JCI data for the period August 2016 - December 2019 on the IDX, and obtained a sample of 41 months. Types of data using quantitative data and data sources using secondary data obtained from Finance.yahoo and www.bi.go.id. The data of this study were analyzed using the multiple linear regression method of time series through the Eviews application version 8. The results showed that the Inflation variable and the BI 7-Day (reverse) Repo Rate variable had a negative and not significant effect on the CSPI, while the Rupiah Exchange Rate had an effect positive and significant effect on the JCI.